Democracy, Stability, and Dichotomies - Bollen, Kenneth A.; Jackman, Robert W. (American Sociological Review, 1989)
An early debate in the empirical study of political democracy concerned the measurement of democracy. Initial work employed dichotomous indicators and incorporated stability into political democracy measures. Evidence accumulated showing that this approach could adversely affect analyses, particularly in the study of income inequality. Despite this, some recent studies have renewed the flawed practices. We draw upon recent work to highlight the confusion that can result when democracy and stability are confounded and the problems with dichotomous indicators. We propose that stability is analytically distinct from political democracy and should be treated as such empirically, and we suggest ways to estimate incremental effects of political democracy. We further argue that political democracy is continuous and that measures of it should reflect this. It is important that the measurement history of this construct not repeat itself.